2004
DOI: 10.1038/sj.bdj.4811648
|View full text |Cite
|
Sign up to set email alerts
|

Five mandibular incisors: an autosomal recessive trait?

Abstract: A fifth mandibular incisor is a eumorphic supernumerary tooth and has rarely been described in the medical literature. We report here a large Lebanese consanguineous family where four individuals displayed five incisors in the anterior mandible. Such familial observation has not been previously described. The possibility of an autosomal recessive inheritance for this nonsyndromic trait is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 5 publications
1
17
0
Order By: Relevance
“…Case reports which have been published earlier have suggested that the supplemental teeth may exhibit deep palatal pits and coronal invaginations, or that when no morphological abnormalities are noted, the tooth with minimum measurement among other anterior teeth is regarded as supernumerary one [5,6]. Interestingly, in our case, both these features stood irrelevant.…”
Section: Acknowledgmentmentioning
confidence: 52%
See 3 more Smart Citations
“…Case reports which have been published earlier have suggested that the supplemental teeth may exhibit deep palatal pits and coronal invaginations, or that when no morphological abnormalities are noted, the tooth with minimum measurement among other anterior teeth is regarded as supernumerary one [5,6]. Interestingly, in our case, both these features stood irrelevant.…”
Section: Acknowledgmentmentioning
confidence: 52%
“…A possible association between supernumerary teeth and aggressive periodontitis has been described, though it is uncommon [9]. Reports made by Odell and Hughes in 1995, attributed them to have familial tendencies, with rare occurrences [6,11,14,15]. Our patient reported to us with periodontitis which was generalized and hence, the existence of aggressive periodontitis was ruled out.…”
Section: Acknowledgmentmentioning
confidence: 63%
See 2 more Smart Citations
“…A male to female ratio of 2:1 is found in populations with single supernumerary teeth [Kantor et al, 1988] which increases to 3:1 for multiple supernumerary teeth [Gibson, 1979]. Although inherited forms are rare, a familial inheritance has been reported that can be autosomal dominant with incomplete penetrance, autosomal recessive [Cassia et al, 2004] or sex linked pattern of inheritance [Burzynski and Escobar, 1983]. …”
Section: Human Tooth Developmental Anomaliesmentioning
confidence: 99%